Understanding Tourism Destination through Music: Digital Engagement Discourse Based on Sentiment Analysis Approach - Singgalen, Yerik Afrianto (STMIK Budi Darma, 2024)
This research investigates the effectiveness of music-video content as a tool for tourism destination marketing, employing the CRISP-DM framework to approach data collection, analysis, and interpretation systematically. Focusing on the music video